2002
DOI: 10.1111/j.1365-2621.2002.tb08835.x
|View full text |Cite
|
Sign up to set email alerts
|

Food Protein Functionality in a Liquid System: A Comparison of Deamidated Wheat Protein with Dairy and Soy Proteins

Abstract: Solubility, surface properties, overrun, foam stability, apparent viscosity, and emulsification properties were evaluated for 3% protein dispersions of deamidated wheat protein (DWP), sodium caseinate (SC), soy protein isolate (SPI), and whey protein isolate (WPI). DWP dispersion had the highest apparent viscosity, 25% higher emulsion activity index (EAI), and 82% higher emulsion stability index (ESI) when compared to SPI dispersions. Dispersions of DWP had similar foaming properties and surface properties whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 31 publications
0
29
1
Order By: Relevance
“…This in part may be attributed to the lower solubility of SPI compared with WPI, as sediment was visually observed during the preparation of SPI dispersions. Webb et al (19) previously reported that the solubility of SPI was significantly lower than WPI, 60.7 and 96.3%, respectively. The reduced solubility of SPI would result in a lower concentration of protein that is available to interact with DGS to form MRP.…”
Section: Colors Of Aqueous Protein-dgs Mixturesmentioning
confidence: 95%
“…This in part may be attributed to the lower solubility of SPI compared with WPI, as sediment was visually observed during the preparation of SPI dispersions. Webb et al (19) previously reported that the solubility of SPI was significantly lower than WPI, 60.7 and 96.3%, respectively. The reduced solubility of SPI would result in a lower concentration of protein that is available to interact with DGS to form MRP.…”
Section: Colors Of Aqueous Protein-dgs Mixturesmentioning
confidence: 95%
“…Protein dispersions and suspensions were analyzed by the turbidometric technique for emulsion activity index (EAI) and emulsion stability index (ESI) as previously described (Webb, Naeem, & Schmidt, 2002). Emulsions were prepared with 3% protein dispersions (w/v) using 10 ml of sunflower oil (Zvijezda d.o.o., Zagreb, Croatia), by mixing for 90 sec in a blender (Philips, model HR 2304).…”
Section: Emulsifying Propertiesmentioning
confidence: 99%
“…The functional properties including antioxidant activity have been studied most extensively for soybean and milk proteins (Chove, Grandison, & Lewis, 2007;Hu et al, 2003;Le Tien, Vachon, Mateescu, & Lacroix, 2001;Tong, Sasaki, McClements, & Decker, 2000;Webb, Naeem, & Schmidt, 2002). Different studies have also been conducted to improve functional properties of these proteins by enzymatic hydrolysis (Chen, Muramoto, & Yamauchi, 1995;Pacheco, Amaya-Farfan, & Sgarbieri, 2002;Penas, Prestamo, & Gomez, 2004).…”
Section: Introductionmentioning
confidence: 99%